Clinical features of congenital myasthenic syndrome due to mutations in DPAGT1. Issue 10 (27th February 2013) - Finlayson, Sarah; Palace, Jacqueline; Belaya, Katsiaryna; Walls, Timothy J; Norwood, Fiona; Burke, Georgina; Holton, Janice L; Pascual-Pascual, Samuel I; Cossins, Judith; Beeson, David
Abstract : Background: A newly defined congenital myasthenic syndrome (CMS) caused by DPAGT1 mutations has recently been reported. While many other CMS-associated proteins have discrete roles localised to the neuromuscular junction, DPAGT1 is ubiquitously expressed, modifying many proteins, and as such is an unexpected cause of isolated neuromuscular involvement. Methods: We present detailed clinical characteristics of five patients with CMS caused by DPAGT1 mutations. Results: Patients have prominent limb girdle weakness and minimal craniobulbar symptoms. Tubular aggregates on muscle biopsy are characteristic but may not be apparent on early biopsies. Typical myasthenic features such as pyridostigmine and 3, 4- diaminopyridine responsiveness, and decrement on repetitive nerve stimulation are present. Conclusions: These patients mimic myopathic disorders and are likely to be under-diagnosed. The descriptions here should facilitate recognition of this disorder. In particular minimal craniobulbar involvement and tubular aggregates on muscle biopsy help to distinguish DPAGT1 CMS from the majority of other forms of CMS. Patients with DPAGT1 CMS share similar clinical features with patients who have CMS caused by mutations in GFPT1, another recently identified CMS subtype.